Peningkatan Kapasitas Pemerintah Desa Pejengkolan sebagai Upaya Pembangunan Berkelanjutan - Isnaini Lilis Elviyanti; Ahamad Aftah Syukron; Titi Maemuna; Dwiyono Waluyo (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Improving the capacity of village government is a strategic step in realizing sustainable development oriented towards community welfare. Pejengkolan Village, Padureso District, Kebumen Regency, as a developing village, faces challenges in planning, managing, and implementing participatory and sustainable development programs. These challenges include limited knowledge of village officials, a lack of understanding of village development regulations, and weak coordination between the village government and village institutions and the community. This research/activity aims to strengthen the capacity of village government officials by increasing knowledge, skills, and understanding of the role of village institutions, particularly the Village Consultative Body (BPD) and Village Community Institutions (LKD), in the development planning process. Capacity building for local government officials is considered a crucial step to ensure sustainable development at the village level. The method used is a participatory approach through training, focus group discussions, and technical assistance. This participatory approach not only improves technical skills but also strengthens collaborative values ​​among stakeholders. The results of the activity demonstrated an increase in village officials' understanding of village development regulations, their ability to develop inclusive development plans, and the establishment of synergy between the village government, the Village Consultative Body (BPD), the Village Funds (LKD), and the community. Furthermore, this activity demonstrated a shift in mindset among village officials toward more transparent, accountable, and responsive governance to community needs. Good governance at the village level is a fundamental element to achieving long-term community welfare. This effort is expected to serve as a foundation for strengthening village governance, which is able to address the dynamic needs of the community and encourage sustainable village development.